Combining ability and heterosis in a diallel cross of safflower under Brazilian tropical conditions - Olivo, Mateus [UNESP]; Bassegio, Doglas [UNESP]; Zanotto, Maurício D. [UNESP] (Wiley, 2020)
Safflower (Carthamus tinctorius) can become an important crop in Brazilian tropical conditions. Combining ability and heterosis of safflower were studied in a five-by-five diallel cross from 2013 to 2015 to determine the nature of gene action. The results indicated significant differences among parents for general and specific combining abilities, except for a number of branches. For plant height, grain yield, number of grains per plant, number of grains per capitulum, and oil content, the contribution of the specific combining ability in the genetic variation was observed in the progenies, showing evidence of nonadditive genetic actions. The results of this study showed that best cross for oil content was PI572450 × PI572470 (27%) with gain over genitors. Combination PI537697 × PI653152 presented promising results for increase grain yield. These superior genotypes could be used in recombination breeding programs to accumulate suitable genes responsible for improving grain yield and oil content under the Brazilian tropical conditions.